An update on the growing evidence base for peer support. Issue 3 (12th June 2017) - Bellamy, Chyrell; Schmutte, Timothy; Davidson, Larry
Abstract : Purpose: As peer support services have become increasingly used in mental health settings as a recovery-oriented practice, so has the body of published research on this approach to care. The purpose of this paper is to provide an update on the current evidence base for peer support for adults with mental illness in two domains: mental health and recovery, and physical health and wellness. Design/methodology/approach: To provide a robust, non-redundant, and up-to-date review, first the authors searched for meta-analyses and systematic reviews. Second, the authors found individual studies not included in any of the reviews. Findings: Peer services are generally equally effective to services provided by non-peer paraprofessionals on traditional clinical outcomes. Although some studies found peer services to be effective at reducing hospitalization rates and symptom severity, as a whole, the current evidence base is confounded by heterogeneity in programmatic characteristics and methodological shortcomings. On the other hand, the evidence is stronger for peer support services having more of a positive impact on levels of hope, empowerment, and quality of life. Research limitations/implications: In addition to the need for further high-quality research on peer support in mental and physical health domains, the authors also question whether measures of hope, empowerment, and integration into the community are more relevant to recovery than traditional clinical outcomes. Originality/value: This paper provides an original, robust, and up-to-date review of the evidence for peer services.